P79 Is length of stay (LOS) equivalent for elective anterior cervical discectomy (ACD) patients in an NHS hospital and as waiting list initiative cases in a private hospital?. Issue 3 (14th February 2019) - Meacock, J; Thomson, S; Derham, C
Abstract : Objectives: To investigate if there is a significant difference between the LOS for patients admitted as waiting list initiative patients to a private hospital versus standard care in an NHS hospital. Design: Retrospective analysis between 2015 and 2017 of all ACD procedures at the two hospitals. Subjects: 674 elective NHS patients were included, 340 were admitted to the NHS hospital and 334 as waiting list initiative patients to the private hospital. Acute patients were excluded. Methods: Retrospective database search of electronic hospital records for all ACD procedures carried out between 2015 and 2017. The student standard t test analysis was used to compare the difference in LOS. Results: In both groups 100% were admitted on the day of surgery. The mean NHS LOS was 3.3 (SD=6.34) days and the private hospital was 1.1 (SD=0.97) days. (p<0.001) For the patients admitted to the private hospital 96% of the patients went home with 1 night stay, only 61% of the patients went home in the same period in the NHS hospital. Conclusions: We found that length of stay is significantly shorter in the private hospital than in the NHS hospital. This could be due to patient selection, a swifter patient pathway or a combination of the two and these factors will be explored.